2020
DOI: 10.1063/1.5144299
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and theoretical studies of UN and UN+

Abstract: The low-energy electronic states of UN and UN+ have been examined using high-level electronic structure calculations and two-color photoionization techniques. The experimental measurements provided an accurate ionization energy for UN (IE = 50 802 ± 5 cm−1). Spectra for UN+ yielded ro-vibrational constants and established that the ground state has the electronic angular momentum projection Ω = 4. Ab initio calculations were carried out using the spin–orbit state interacting approach with the complete active sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Several computational studies have been reported for uranium-containing diatomic molecules. The electronic structure of uranium monohydride (UH) resembles those of UF and UCl, which can be considered ionic U + X – ; the uranium cation is perturbed by a closed-shell anion ligand. Bross and Peterson obtained a 4 I 9/2 (U + (5f 3 7s 2 ) ground state for UF and UCl from high-level correlated molecular orbital theory calculations, in agreement with previous calculations on UF by Antonov and Heaven using the CASPT2-SO approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several computational studies have been reported for uranium-containing diatomic molecules. The electronic structure of uranium monohydride (UH) resembles those of UF and UCl, which can be considered ionic U + X – ; the uranium cation is perturbed by a closed-shell anion ligand. Bross and Peterson obtained a 4 I 9/2 (U + (5f 3 7s 2 ) ground state for UF and UCl from high-level correlated molecular orbital theory calculations, in agreement with previous calculations on UF by Antonov and Heaven using the CASPT2-SO approach.…”
Section: Introductionmentioning
confidence: 99%
“…Polynomials remain a popular choice of model function. [13] In the present strategy, we include a high-resolution potential energy function computed using a less expensive, presumably lower-level theoretical method. This provides the physics used to guide the interpolation of the high-level data.…”
Section: 𝐸 𝑅mentioning
confidence: 99%
“…New approaches in synthetic chemistry have produced a variety of ligated uranium–nitrogen complexes. Isolated uranium nitrides and uranium–nitrogen complexes have been studied with infrared spectroscopy of species produced in rare gas and nitrogen matrixes. Unfortunately, gas phase spectroscopy on uranium–nitrogen compounds is quite limited. The UN diatomic has been studied by using resonant photoionization spectroscopy. , Bowen and co-workers recently reported the photoelectron spectrum of the uranium dinitride anion . This study revealed a closed-shell electronic structure for the corresponding neutral with uranium in the +6 oxidation state, isoelectronic with the uranyl cation.…”
Section: Introductionmentioning
confidence: 99%
“…The UN diatomic has been studied by using resonant photoionization spectroscopy. 46,47 Bowen and co-workers recently reported the photoelectron spectrum of the uranium dinitride anion. 48 This study revealed a closed-shell electronic structure for the corresponding neutral with uranium in the +6 oxidation state, isoelectronic with the uranyl cation.…”
Section: ■ Introductionmentioning
confidence: 99%